(3GdeUfas - (3YHO GdQGRb Hf geGe GdUZGfjs
(3ChdgG (B:s
(3jHOC HHGH GdQLd jJhJQ Ke jSJjbX ajQjO Cf jUdi s
(3BNQgG (B:s
(3jfJgi HChd cJGH aVGFd GdbQBf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1712s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs